Exergetic, economic and carbon emission studies of bio-olefin production via indirect steam gasification process - Jiang, Peng; Parvez, Ashak Mahmud; Meng, Yang; Xu, Meng-xia; Shui, Tian-chi; Sun, Cheng-gong; Wu, Tao (2019)
The indirect steam gasification of biomass to olefins (IDBTO) coupled with CO2 utilization was proposed and simulated. Energy and exergy efficiencies, net CO2 emissions, and economic evaluation were performed against IDBTO as well as the direct oxygen-steam gasification of biomass to olifins (DBTO). The influences of unreacted gas recycling fraction (RU) and CO2 to dry biomass mass ratio (CO2/B) on the thermodynamic performance of the processes were also studied. The results showed that the yields of olefins of DBTO and IDBTO were 17 wt% and 19 wt%, respectively, the overall energy and exergy efficiencies of the IDBTO were around 49% and 44%, which were 8% and 7% higher than those of the DBTO process, respectively. A higher RU was found favor higher energy and exergy efficiencies for both routes. Besides, for the IDBTO process, it is found that the addition of CO2 to gasification system led to an improvement in both energy efficiency and exergy efficiency by around 1.6%. Moreover, life-cycle net CO2 emission was predicted to be -4.4 kg CO2 eq./ kg olefins for IDBTO, while for DBTO, it was -8.7 kg CO2 eq./ kg. However, the quantitative economic performance of IDBTO was superior to that of the DBTO process.